PENGARUH PUNISHMENT DAN REWARD TERHADAP MOTIVASI BELAJAR SERTA IMPLIKASINYA TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI - Siwi Andriyani Amatilah; Yoni Hermawan; Rendra Gumilar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was motivated by the low learning motivation of class indicating that the students' learning outcomes are low. This research aims to determine the effect of punishment and reward on students' learning motivation and their implications for students' learning outcomes. This research is quantitative research using a survey method with an explanatory design. The population of this study was all students in class XI, totaling 439. The sampling technique was simple random sampling. The sample taken was 209 students. Data was obtained from distributing questionnaires and analyzed using path analysis with the help of the Amos Version 26 application. The results of research on direct influence show that punishment has an effect on learning motivation, reward has an effect on learning motivation, punishment has an effect on participants' learning outcomes, rewards have an effect on results. learning, learning motivation influences student learning outcomes, punishment influences learning outcomes through learning motivation, and rewards influence learning outcomes through learning motivation.